The Preliminary Dating of the Bidong Shipwreck, Malaysia - Muhamed, Kamarul Redzuan (The international journal of nautical archaeology, 2025)
The Bidong shipwreck, discovered in 2012, is like a time capsule with much information. A total of 306 ceramics and some wood samples were recovered during the first (2017) and second (2022) phases of excavation. Three main dating techniques were used in this study. A relative dating was conducted by comparative analysis of 10 intact ceramics with published reports, museum archives, and expert consultation. The recovered ceramics were identified as Thai Si Satchanalai and Maenam Noi ceramics. The samples were analysed for absolute dating of Thermoluminescence (TL), suggesting the ceramics were produced in 1500–1700 CE. Radiocarbon dating of wood suggested two periods of time: 1395–1444 CE for the ship’s frame and 1437–1522 CE for the ship’s plank. Based on relative and absolute dating, the preliminary date of the Bidong shipwreck is estimated between 1500 and 1550 CE.